Creating Impact : The Promise of Impact Investing - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
This report takes stock of the market for impact investing and examines the conditions that would allow the market to grow and realize its potential. Historically, there have always been investors who cared about more than just financial returns. Governments and philanthropists, for example, have set up investment vehicles with mandates to promote social and environmental goals. Over the last decade, impact investing has gained prominence as an approach to investment that aims to achieve both financial returns and social or environmental goals.1 This has created a dynamic but somewhat disorganized market of diverse participants, standards, and concepts. Although still small, the market is attracting considerable interest, and it has the potential to increase in scale, and thereby contribute to the achievement of the Sustainable Development Goals (SDGs) and the Paris climate goals.